Exploring entrepreneurial intention among Chinese student in Malaysia using TPB - Robuan, Mohd Rashan Shah (International Journal of Accounting, Finance and Business, 2024)
The objective of this study is to explore the determinants factor influencing entrepreneurial intentions among Chinese ethnic students who have completed compulsory entrepreneurship education courses. Using a quantitative approach, the research evaluates the propensity towards entrepreneurship through TPB within the Chinese ethnic groups in Malaysia. The data analysis utilized Statistical Package for Social Sciences (SPSS) and Smart PLS4 software to comprehensively examine and interpret the findings. The result showed that only personal attitudes and subjective norm influence the entrepreneurial intention of the Chinese students. The study showed to increase the intention of the Chinese student in entrepreneurial activities they should be collaboration with the entrepreneur and industry.